Dormancy‐to‐death transition in yeast spores occurs due to gradual loss of gene‐expressing ability - Théo Maire; Tim Allertz; Max A Betjes; Hyun Youk (Molecular Systems Biology)
Abstract Dormancy is colloquially considered as extending lifespan by being still. Starved yeasts form dormant spores that wake‐up (germinate) when nutrients reappear but cannot germinate (die) after some time. What sets their lifespans and how they age are open questions because what processes occur—and by how much—within each dormant spore remains unclear. With single‐cell‐level measurements, we discovered how dormant yeast spores age and die: spores have a quantifiable gene‐expressing ability during dormancy that decreases over days to months until it vanishes, causing death. Specifically, each spore has a different probability of germinating that decreases because its ability to—without nutrients—express genes decreases, as revealed by a synthetic circuit that forces GFP expression during dormancy. Decreasing amounts of molecules required for gene expression—including RNA polymerases—decreases gene‐expressing ability which then decreases chances of germinating. Spores gradually lose these molecules because they are produced too slowly compared with their degradations, causing gene‐expressing ability to eventually vanish and, thus, death. Our work provides a systems‐level view of dormancy‐to‐death transition.